Influence of Heat Generation/Absorption on the Nonlinear Convective Flow of a Casson Fluid over a Horizontal Plate - Kairi, R. R.; Ramreddy, Ch.; Roy, S. (Discontinuity, Nonlinearity, and Complexity, 2026)
This work highlights the influence of nonlinear mixed convective flow of a non-Newtonian fluid over a horizontal plate in the presence of heat generation/absorption. The Casson fluid model is employed to express the non-Newtonian behavior of the fluid. Also, the density of the Casson fluid is assumed to be a nonlinear function of temperature. The boundary layer analysis is adopted by introducing a set of non-dimensional transformations for deriving the non-dimensional form of flow governing equations. The proposed problem does not permit a similarity solution. Thus, local similarity and local non-similarity methods are adopted to convert the set of nonlinear PDEs to the set of nonlinear ODEs. On account of local similarity and non-similarity method, the consequential ODEs are solved numerically by the Runge-Kutta method together with the shooting technique. The control of pertinent parameters on the velocity and temperature fields, and on the non-dimensional heat transfer rate as well as on the skin friction coefficient, are analyzed through graphical representation and explored in detail. Prior knowledge about the effect of these parameters on the heat transfer rate and skin friction coefficient can be very useful in the perspective of industrial applications.